Efficient dual-ions hybrid capacitive system for superior deionization with enhanced kinetics match. (20th December 2022) - Han, Deng-Cheng; Wang, Si-Yu; Zhang, Chun-Miao; Yue, Reng-Yu; Wang, Shu-Guang; Sun, Xue-Fei
Highlights: A dual-ions hybrid capacitive deionization system aided by BiOCl depicted superior desalination performance. Low-cost raw materials, high specific capacity, and great cyclability to desalination have been achieved. The enhanced kinetics of capacitive/redox electrodes in the HCDI system were revealed. Abstract: Capacitive deionization (CDI) is regarded as a promising water purification technology to tackle the global water crisis challenges. However, CDI technology is limited by the low capacity of harvesting more ions from highly concentrated feed water. This can be solved by coupling appropriate cathode with anode materials to enhance kinetics and capacities. In this study, a dual-ion hybrid capacitive deionization (HCDI) system was designed and constructed to enhance the charge efficiency and desalination capacity. The system consists of a BiOCl redox electrode and a capacitive electrode made of graphene-based MnO2 nanorods composite (MnGA). The BiOCl redox electrode was used to capture chloride ions and the MnGA capacitive electrode was employed to form an electric double layer for trapping sodium ions during discharging processes. It was found that a better capacitive electrode could realize the full potential of the counter redox electrode in the HCDI system. Consequently, the assembled dual-ion MnGA||BiOCl HCDI system showed enhanced kinetics characteristics in high-concentration NaCl solution with desalination capacity reaching 69.18 mg/g and charge efficiency of up to 75.21%. The satisfying kinetic match between anode and cathode has achieved optimized charge balance, which maximized the electrochemical performance of the HCDI system. This HCDI system was able to improve utilization efficiency, enhance desalination capacity, and achieve good stability at a low cost. Hence, it is promising for future practical deionization applications. Graphical abstract: Image, graphical abstract